Correlation of Spot Urine Albumin to Creatinine Ratio and 24-Hrs. Urinary Protein Excretion in Pregnancy Induced Hypertension Cases - Naheed Parveen, Erum Siddiqi, Shazia Awan, Madiha Abbasi, Roohi Nigar, Mehwish Baloch, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Preeclampsia remains a leading cause of maternal morbidity and mortality worldwide. 24-hour urinary protein estimation remains the gold standard method for the diagnosis of preeclampsia. However, there was a controversy in the existing literature regarding the positive predictive value of spot urinary protein to creatinine ratio, which caused the present study. Aim: The aim of this study was to determine the positive predictive value of spot urinary protein to creatinine ratio for the diagnosis of preeclampsia taking 24-hour urinary protein as the gold standard. Study Design: It was a cross-sectional survey. Setting: Research was conducted at the Department of Obstetrics & Gynecology Civil Hospital, Hyderabad. Duration: 6 months after the approval of synopsis 17th October 2020 to 16th April 2021 Material and Methods: This study involved 114 pregnant women aged between 18-40 years presenting for a routine antenatal checkup after 28 weeks of gestation (as per dating scan) and having raised blood pressure ≥160/110mmHg on at least two occasions at least 4 hours apart. Preeclampsia was suspected if the spot urinary protein to creatinine ratio was ≥0.2. 24-hour urinary protein excretion was estimated and diagnosis of preeclampsia was confirmed if it was ≥300mg in 24 urine specimens. Results: The mean age of the women was 26.6±6.2 years while the mean gestational age was 34.3±1.6 weeks. 26 (22.8%) women were primiparas and 88 (77.2%) women were multiparas. The mean BMI of these women was 26.7±4.2 Kg/m2 and 32 (28.1%) women were obese. Diagnosis of preeclampsia was confirmed in 111 (97.4%) women on 24-hour urinary protein excretion. It yielded a positive predictive value of 97.4% for spot urinary protein to creatinine ratio in the diagnosis of preeclampsia, taking 24-hour urinary protein excretion as the gold standard. A similar positive predictive value was noted across various subgroups of women based on age, gestational age, parity, and BMI. Conclusion: In the present study, the positive predictive value of spot urinary protein to creatinine ratio was found to be 97.4% in predicting preeclampsia in hypertensive pregnant women regardless of patient’s age, gestational age, parity, and BMI which along with the associated advantage of spot specimen collection and timely results (compared to the routine practice of 24-hour urinary protein estimation which wastes precious time and delays the patient’s treatment), advocates the preferred use of spot urinary protein to creatinine ratio in the evaluation of hypertensive pregnant women in future obstetric practice.